Hidden systems : water, electricity, the internet, and the secrets behind the systems we use every day - Nott, Dan (Random House Graphic, 2023)
"What was the first message sent over the internet? How much water does a single person use every day? How was the electric light invented? For every utility people use each day, there's a hidden history below the surface - a story of intrigue, drama, humor, and inequity. This graphic novel provides a guided tour through the science of the past - and how the decisions people made while inventing and constructing early technology still affect the way people use it today. Full of art, maps, and diagrams, Hidden Systems is a thoughtful, humorous exploration of the history of science, and what needs to be done now to change the future"--